Physiotherapeutic Applications of Biomechanical Opposing Indicators - Based on Measurements of Taekwon-Do Athlets - Jacek Wąsik; Dorota Ortenburger; Tomasz Góra (Lesya Ukrainka Volyn National University, 2017)
Background. In everyday life people constantly face the dilemma of speed and accuracy. The aim of the cognitive quantification was to increase the knowledge about kinematic effect of a target. The practical aim would be to apply kinematic effect of a target in clinical situations, to supply for physiotherapeutic programs. Material and Method. The analysis was performed 14 taekwondo ITF athletes. During research they performed front left and right kicks in a lateral standing position: into the air (without a physical target), to a table tennis ball hanging on a line and a training target. The laboratory for the analysis of movement named HML was used here. Results. The highest average maximum velocity was obtained by the kicks without a physical target (10,78 - 1,32 m/s for men and 8,51 - 1,50 m/s for women)(p<0,05), then to the shield (9,98 - 1,40 m/s for men and 8,28 - 1,59 m/s for women) (p<0,05) and to the ball (9,63 -0,94 m/s for men 7,73 - 2,01 m/s for women) (p<0,05). Discussion.The obtained results provided the argument supporting the thesis that the type of target influences on the method of solving the dilemma: the velocity of movement and its precision during a frontal kick. Both, in the case of women and men who practisetaekwon-do, lowering the velocity of a kick, performed towards a precisely established target, in comparison with the velocity of a kick without a precisely established physical target (into the air) was observed. For many people with the dysfunctions of the movement organs, everyday functioning, especially related to movement, makes a challenge. In such a case crossing the road at the green light in particular time or stepping on the escalator (the examples of such barriers are numerous) are the tasks that reveal the dilemma of velocity and precision. There are many factors that may support the efficiency of these efforts. One of them may be the feeling of the efficiency of activity that has a psychological character.